Association of VEGFA polymorphisms with necrotizing enterocolitis in Chinese Han population - Xiaoyan Gao; Fei Ma; Hu Hao; Yiheng Dai; Weidong Liu; Xin Xiao; Pingmin Gao; Sitao Li (Pediatrics and Neonatology)
Background: To examine whether polymorphisms in the VEGFA gene lead to low VEGFA production in peripheral blood and increased risk of NEC in the Chinese Han population. Material and methods: Thirty NEC patients and 80 control subjects were enrolled. Six VEGFA single-nucleotide polymorphisms (SNPs) were performed using the SEQUENOM MassARRAY platform assay. The concentration of VEGFA in the plasma was measured using an enzyme-linked immunosorbent assay. Results: The rs699947 and rs833061 VEGF-A SNPs were found to be associated with low plasma levels and high risk of NEC. Conclusion: Our results suggested that, if validated in larger studies, screening for VEGFA SNPs and plasma levels might be useful as a risk factor for NEC in the future. Key Words: necrotizing enterocolitis, preterm infants, single-nucleotide polymorphism, VEGFA